Efek Menguntungkan Dari Medan Elektromagnetik - Muhammad Dicky Saputra; Andi Purwanto; Danna Rayana; Aulivia Widya Putri; Diyajeng Luluk Karlina (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This study examines the intense competition in the contemporary franchise beverage industry in Gorontalo City, where consumers have many choices that affect loyalty to certain brands. This study aims to analyze the effect of brand equity and marketing mix on customer loyalty. This descriptive quantitative research uses accidental sampling with 100 samples. Data analysis includes statistical tests as well as Structural Equation Modeling (SEM) models. This study shows that brand equity and marketing mix have a positive and significant effect on purchasing decisions, both partially and simultaneously, with the t-count and f-count values exceeding the table limit at the 95% confidence level. SEM-PLS analysis confirmed the significant relationship with p-values of 0.05 and t-statistics of 1.96, supporting the tested model. The research conclusion shows that brand equity and marketing mix have a significant influence on purchasing decisions. As advice, business owners of contemporary beverage franchises in Gorontalo City are advised to strengthen brand equity, as well as optimize creative and effective marketing strategies to increase competitiveness.